The Role of GCN2 Kinase in Mediating the Effects of Amino Acids on Longevity and Feeding Behaviour in Drosophila - Srivastava, Anchal; Lu, Jiongming; Gadalla, Dennis Said; Hendrich, Oliver; Grönke, Sebastian; Partridge, Linda (Frontiers in Aging, 2022)
Restriction of amino acids in the diet can extend lifespan in diverse species ranging from flies to mammals. However, the role of individual amino acids and the underlying molecular mechanisms are only partially understood. The evolutionarily conserved serine/threonine kinase General Control Nonderepressible 2 (GCN2) is a key sensor of amino acid deficiency and has been implicated in the response of lifespan to dietary restriction (DR). Here, we generated a novel Drosophila GCN2 null mutant and analyzed its response to individual amino acid deficiency. We show that GCN2 function is essential for fly development, longevity and feeding behaviour under long-term, but not short-term, deprivation of all individual essential amino acids (EAAs) except for methionine. GCN2 mutants were longer-lived than control flies and showed normal feeding behaviour under methionine restriction. Thus, in flies at least two systems regulate these responses to amino acid deprivation. Methionine deprivation acts via a GCN2-independent mechanism, while all other EAA are sensed by GCN2. Combined deficiency of methionine and a second EAA blocked the response of GCN2 mutants to methionine, suggesting that these two pathways are interconnected. Wild type flies showed a short-term rejection of food lacking individual EAA, followed by a long-term compensatory increase in food uptake. GCN2 mutants also showed a short-term rejection of food deprived of individual EAA, but were unable to mount the compensatory long-term increase in food uptake. Over-expression of the downstream transcription factor ATF4 partially rescued the response of feeding behaviour in GCN2 mutants to amino acid deficiency. Phenotypes of GCN2 mutants induced by leucine and tryptophan, but not isoleucine, deficiency were partially rescued by ATF4 over-expression. The exact function of GCN2 as an amino acid sensor in vivo and the downstream action of its transcription factor effector ATF4 are thus context-specific with respect to the EAA involved.